EVALUASI PENERAPAN SISTEM PEMBAYARAN DENDA NON TUNAI DI PERPUSTAKAAN PERGURUAN TINGGI BERDASARKAN PERSPEKTIF PENGGUNA (STUDI KASUS UPT PERPUSTAKAAN UNIVERSITAS ANDALAS) - Andi Saputra (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2019)
To support Perpres no. 87 of 2016, regarding the task force for sweeping illegal levies, the rector of Andalas University in 2017 had issued a system of payment of cashless at the Unand Library Unit. All fine payment transactions are paid through the rector's account which is deposited in Bank Nagari who is a partner of Unand. This study aims to evaluate the policy from the perspective of students as the main users of college library services. Data collection is done using a questionnaire that is distributed to users who have paid fines at the bank. Sample selection was done by purposive random sampling without distinguishing the class and level of study. The results showed that this policy turned out to cause new problems among users. Most students object to the system of paying non-cash fines. They considered this policy to be less effective and tended to harm students both in terms of time and cost, because the Bank Center was quite far from the library building. Actually the use of EDC machines is able to overcome these problems, but the ATM card of the bank that provides the EDC machine, in accordance with the holding account, among Unand students the percentage is still small (24%). To overcome the impact of the non-cash payment system the majority of students (50.65%) suggested returning the payment system at the book return counter, and 31.65% suggesting adding another bank's EDC machine.